"Eau de graphene" from a KC8 graphite intercalation compound prepared by a simple mixing of graphite and molten potassium. Issue 12 (5th December 2016) - Bepete, George; Hof, Ferdinand; Huang, Kai; Kampioti, Katerina; Anglaret, Eric; Drummond, Carlos; Pénicaud, Alain
Abstract : We synthesized KC8 by simply mixing molten potassium and graphite at 180 °C under inert atmosphere. The KC8 shows typical shiny bronze color, Raman characteristics and XRD pattern of an efficiently intercalated stage 1 GIC, and is of sufficient quality to produce fully exfoliated graphenide solutions in tetrahydrofuran (THF) and subsequently single layer graphene in water as "eau de graphene" (EdG). The evolution of absorption and Raman spectroscopic signatures of the EdG as a function of processing conditions give key indications on the number of layers of the graphene flakes dispersed in EdG. (© 2016 WILEY‐VCH Verlag GmbH &Co. KGaA, Weinheim) Abstract : KC8 graphite intercalation compound was efficiently prepared by simply mixing graphite flakes and molten potassium metal at 180 °C under inert atmosphere. The KC8 can be readily exfoliated down to single layers in tetrahydrofuran (THF), yielding graphenide solutions. "Eau de graphene" (EdG) was subsequently obtained by mixing graphenide solutions with degassed water and evaporating the THF. Deposits from EdG on freshly cleaved mica show predominantly monolayer graphene flakes.